A Curated Database of miRNA Mediated Feed-Forward Loops Involving MYC as Master Regulator - El Baroudi, Mariama; Corà, Davide; Bosia, Carla; Osella, Matteo; Caselle, Michele (PLOS ONE, 2011)
Background The MYC transcription factors are known to be involved in the biology of many human cancer types. But little is known about the Myc/microRNAs cooperation in the regulation of genes at the transcriptional and post-transcriptional level. Methodology/Principal Findings Employing independent databases with experimentally validated data, we identified several mixed microRNA/Transcription Factor Feed-Forward Loops regulated by Myc and characterized completely by experimentally supported regulatory interactions, in human. We then studied the statistical and functional properties of these circuits and discussed in more detail a few interesting examples involving E2F1, PTEN, RB1 and VEGF. Conclusions/Significance We have assembled and characterized a catalogue of human mixed Transcription Factor/microRNA Feed-Forward Loops, having Myc as master regulator and completely defined by experimentally verified regulatory interactions.